2011
DOI: 10.1167/iovs.10-6618
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-Associated Cross-Linked Actin Network Formation in Human Trabecular Meshwork Cells Involves β3 Integrin Signaling

Abstract: DEX-associated CLANs were structurally similar to those induced by mAb AP-5 and involved both increased expression and activation of αvβ3 integrins. Thus, glucocorticoid-induced CLAN formation may involve enhanced β3 integrin signaling in HTM cells, possibly by an inside-out signaling mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(128 citation statements)
references
References 30 publications
6
119
1
Order By: Relevance
“…This lack of colocalization contrasted with filamin A whose localization completely mirrored F-actin labeling in earlier studies (5). Overall, DEX increased CLAN formation in TM cells as previously reported [13] from 3 Ϯ 3% in ethanol-treated cells to 10 Ϯ 5% in DEX-treated cells (p Ͻ 0.0001).…”
Section: Fig 2 Distribution Of Proteins In Htm Culturessupporting
confidence: 83%
See 3 more Smart Citations
“…This lack of colocalization contrasted with filamin A whose localization completely mirrored F-actin labeling in earlier studies (5). Overall, DEX increased CLAN formation in TM cells as previously reported [13] from 3 Ϯ 3% in ethanol-treated cells to 10 Ϯ 5% in DEX-treated cells (p Ͻ 0.0001).…”
Section: Fig 2 Distribution Of Proteins In Htm Culturessupporting
confidence: 83%
“…It has been previously shown that activation of ␤3 integrin can trigger CLAN formation in nonglaucomatous cells (4,5), and that this protein is up-regulated and activated on the cell surface following DEX treatment (13). Previous work has also shown that treatment with the PI-3 kinase inhibitor LY294002 significantly decreased CLAN formation (4).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Modulation of ECM composition that controls TM elasticity and compliance may be important to normal function [44]. Studies implicate changes in cell [45][46][47][48] and ECM stiffness as probable factors in the glaucoma process. Recent elastic modulus determination in normal and glaucoma has indicated a relationship of increased TM tissue stiffness to OAG [49][50][51], a change also suggested by clinical studies [52][53][54].…”
Section: Introductionmentioning
confidence: 99%